Rural Community Gardens: The Case of Jurovski Dol in Slovenske gorice - Vovk, Ana; Davidović, Danijel (Podeželje, 2026)
Community gardens, traditionally associated with urban environments, are increasingly emerging in rural areas, where they play a vital role in promoting sustainable lifestyles and improving quality of life. Their contribution goes beyond food production, as they positively impact social cohesion, environmental sustainability, economic resilience, and public health. The paper includes a case of good practice: an initiative by investors in a new residential neighborhood in Jurovski Dol (northeastern Slovenia), where the plan also includes the establishment of rural urban gardens. For the planning of rural community gardens, we use the PermaPlan tool, which integrates LIDAR data with permaculture practices. The findings confirm that community gardens in rural areas represent a holistic solution to many modern challenges and hold significant potential for long-term integration into rural development policies.